Playful activities that create a dynamic environment which fosters english listening and speaking skills at La Colonia Elementary School with students from 6 to 12 years old, 2017 - Santamaría Montes, María Soledad; De Gracia, Edward (David, Panamá : UDELAS, 2017)
El proyecto esta enfocado en niños y niñas a entender y reforzar el inglés de una manera divertida, y beneficiará a los alumnos de la escuela primaria La Colonia.
GENERAL INDEX CHART INDEX GRAPH INDEX INTRODUCTION CHAPTER I: Refential framework of the project CHAPTER II : Description of the project 2.1. Theoretical framework 2.1.1. Playful activities 2.1.2. Dynamic environment 2.1.3. Listeningskills 2.1.4. Speaking skills 2.1.5. Benefits of applying playful activities in classes 2.2. Proposal intervention 2.3. Organizational structure of the project management 2.4. Opeerational specification of the done activities and tasks 2.5. Project products 2.6. Project development chronogram 2.7. Budget CHAPTER III: Resultus analysis Conclusion Recommendations References Annexes
Incluye General Index
Incluye Graph Index
Incluye Chat Index
Documento presentado para optar por el Título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
Keywords: INGLÉS -- PROYECTO DE LICENCIATURA; ENGLISH -- PROYECTO DE LICENCIATURA; LISTENING -- PROYECTO DE LICENCIATURA -- SPEAKING; FACULTAD DE EDUCACIÓN ESPECIAL Y PEDAGOGÍA; ESCUELA DE EDUCACIÓN ESPECIAL; LICENCIATURA EN DOCENCIA EN INGLES; LA COLONIA ELEMENTARY SCHOOL